Purification, crystallization and preliminary crystallographic analysis of a thermostable endonuclease IV from Thermotoga maritima - Hughes, Ronny C. (International Union of Crystallography, 2009)

(untitled)
The DNA-repair enzyme endonuclease IV from the thermophilic bacterium Thermotoga maritima MSB8 (reference sequence NC_000853) has been expressed in Escherichia coli and crystallized for X-ray analysis. T. maritima endonuclease IV is a 287-amino-acid protein with 32% sequence identity to E. coli endonuclease IV. The protein was purified to homogeneity and was crystallized using the sitting-drop vapor-diffusion method. The protein crystallized in space group P6(1), with one biological molecule in the asymmetric unit, corresponding to a Matthews coefficient of 2.39 Å(3) Da(−1) and 47% solvent content. The unit-cell parameters of the crystals were a = b = 123.2, c = 35.6 Å. Microseeding and further optimization yielded crystals with an X-ray diffraction limit of 2.36 Å. A single 70° data set was collected and processed, resulting in an overall R (merge) and a completeness of 9.5% and 99.3%, respectively.